Gestão de recursos hídricos em regiões semiáridas com alta variabilidade de deflúvios superficiais: análise comparativa entre o Ceará no Nordeste do Brasil e o Leste da Austrália - Canamary, Beatriz Costa (2013)
The peculiarities of each country lead to the use of various mechanisms of water allocation. There is no general rule for solving the problem of water scarcity. Understanding the models experienced internationally, identifying their respective advantages and disadvantages are very useful. The main objective of water management is to attend the demand, considering the possibilities and limitations of water supply. However, for this, it is necessary to know all hydrological, climatological and physical aspects of the region to conduct a proper planning of water supply, beyond the knowledge of the population and the multiple interests, to a good demand sizing. However, when the water system is supplied by spatial and temporal variability of inflows, as in semiarid regions, the choice of an effective model for water management becomes more complex, due to the uncertainties presented in evaluating future water levels. In these cases, uncertainties have an important role in water resources management. In the matter of a deep study of water resources management in these regions of high climate variability, models applied in Northeast Brazil and Australia were used as analysis. This paper presents the similarity of climate aspects, the similar problems faced by each region, and finally draws a parallel comparing different methods of available water management.